Efektivitas Pelayanan Administrasi Pendaftaran Tanah di Kantor Pertanahan Kabupaten Manggarai - Riska Irwan; Jacoba D. Niga; David W. Rihi; Jacob Wadu (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This research is entitled The Effectiveness of Land Registration Administration Services at the Manggarai Regency Land Office. This research was conducted with the aim of determining the effectiveness of land registration administration services at the Manggarai Regency Land Office. The research used in this study has a qualitative descriptive approach. This study examines the effectiveness of land registration administrative services, which focuses on inputs, processes, outputs and productivity. The results of this study show that the Manggarai Regency Land Office faces various challenges in land registration services, such as old buildings, limited space and equipment, and funding that depends on the State Budget with limited allocation. The main obstacles include low public understanding of the procedures and benefits of land certificates as well as administrative constraints. The implementation of registration is supported by digitalization and regulations such as Permendagri Number 18 of 2021, but there are still technical obstacles such as limited measuring tools, differences in land use data, and the risk of double certificates. Communication with applicants who are far from the office and delays in announcing results also hinder the public objection process. Indigenous peoples with their own legal structures are a challenge in the PTSL program due to a lack of understanding and cooperation, as well as a reliance on more affordable costs. However, the Land Office managed to meet the registration target with most of the processes being on time and services being considered good, supported by digital innovations that increase efficiency, transparency, and reduce land tenure practices.